CONVERTING KITCHEN WASTE INTO CARBON USING KITCHEN WASTE CARBONIZER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 24 January 2016 - A group of researchers from Universiti Sains Malaysia (USM) led by the Dean of the School of Mechanical Engineering, Professor Dr. Zainal Alimuddin Zainal Alauddin has produced a kitchen waste carboniser (KWC) system which is capable of converting kitchen waste into carbon.